Health Promotion Activity “Safe Medicine at Home? Starting from DAGUSILABU” at the Nurul Islam Islamic Boarding School (PPPM) in Samarinda: Kegiatan Promosi Kesehatan “Obat Aman di Rumah? Mulai dari DAGUSILABU” di Pondok Pesantren Pelajar dan Mahasiswa (PPPM) Nurul Islam Samarinda - Ibrahim, Arsyik; Nurmala, Otsuka Khaera; Ardani, Ana Fauziyyah Rizqullah; Khoirunnisa, Khoirunnisa; Rosalia, Sheilla (B-Creta Publisher, 2025)
Indonesian society has a long-standing practice of utilizing various types of drugs for the treatment of diseases, the management of health conditions, and as dietary supplements. However, there is a lack of awareness regarding proper utilization and disposal of these substances. According to data from the Central Statistics Agency (BPS) in 2024, there was an 8% increase in drug abuse cases compared to the previous year. DAGUSILABU: DApatkan, GUnakan, SImpan, piLAh, dan BUang (Obtain, Use, Store, Sort, and Dispose) is an initiative aimed at enhancing public comprehension of optimal medication management practices. The objective of this initiative is to impart knowledge and cultivate comprehension among the general public regarding the significance of proper medication acquisition, utilization, storage, sorting, and disposal practices to students enrolled in Islamic boarding schools, high school students, and Nurul Islam University students. pharmaceutical education. The results demonstrated a 33% increase in knowledge about DAGUSILABU after the presentation of the material, from 64% to 97%, which can be categorized as good.